EELIS Elementary Encyclopaedia of Library and Information Science. By Pandey S.K. Sharma. Scalable Knowledge Solutions, Faridabad. 2021. 688 p. 2021. Rs. 3500 (Hardbound). 978-81-954374-0-5. - Harinarayana, N. S. (Journal of Information and Knowledge, 2022)
No Abstract.